Case Study for the laboring woman - physiological delivery using the International Classification for Nursing Practice - ICNP®. - Kunz, Aneta; Wieczorek - Wójcik, Beata; Kilańska, Dorota; Hir, Małgorzata (Nursing Problems / Problemy Pielęgniarstwa, 2015)
The competence of a midwife as regards the pregnancy care and delivery management result from the Bill on the nurse and midwife profession of July 15. 2011. The pregnant woman has the right to choose the midwife to cooperate with on the delivery plan to specify, among others, the preference on how the childbirth should be organised. The delivery plan can be modyfied by the person taking care of the woman in labour in line with her current health condition. The woman and her partner will expect of the midwife in the labour ward to be professional, which is synonymous with safety. The midwife has an extensive knowledge of delivery distortion factors and should focus on detecting and eliminating the risk factors, early danger detection and solving currently encountered problems. The main goal of midwife care, both during pregnancy as well as in labour and postpartum period, is to safeguard the mother and the child and to prevent from any distortion with their health. The aim can be achieved by the midwife through the nurturing process. The method not only conditions the supervision of the mother in childirth but also makes the regular readings evaluation easier, which influences the change in the supervisory care plan. According to the International Nursing Board Recommendation, a midwife can develop her care plan based on the International Classification for Nursing Practice (ICNP®), making use of standardised diagnoses and interventions. Research shows that making use of standards and reference terminology improves the care quality and treatment results, also through unification of document management. Nursing Topics 2015; 23 (4): 557–562